A Localized Phage-Based Antimicrobial System: Effect of Alginate on Phage Desorption from β-TCP Ceramic Bone Substitutes - Rached Ismail; Natalia D. Dorighello Carareto; Jean-Christophe Hornez; Franck Bouchart (MDPI AG, 2020)
Tricalcium phosphate (TCP) is a prosthetic material commonly used as a bone substitute to repair osteoarticular diseases and injuries. In this type of bone reconstruction surgery, antibiotics remain the common preventive and therapeutic treatment for bacterial infection. Nevertheless, the emergence of multi-resistant strains requires complimentary or alternative treatments. Today, one of the promising alternative approaches is phage therapy. Phages are bacterial viruses that have several advantages over chemotherapy, such as the specificity of bacterial strain, the absence of side effects, and a rapid response. In this work, we studied the impact of alginate hydrogels for overlaying λvir-phage-loaded β-TCP ceramic bone substitutes, delaying the phage desorption. The results show that the use of a 1% alginate-CaCl2 hydrogel overlapping the β-TCP ceramic pellets leads to higher initial phage concentration on the material and extends the released time of phages to two weeks when compared with control pellets. These alginate-coated biomaterials also generate faster bacterial lysis kinetics and could therefore be a good practical prosthetic device for bone and joint surgeries by allowing local treatment of bacterial infections with phage therapy for a longer period of time.